Influence of the addition of synthetic termite saliva in the compressive strength and water absorption of compacted soil-cement - Faria, Obede Borges; Battistelle, Rosane Aparecida Gomes; Neves, Célia (Associação Nacional de Tecnologia do Ambiente Construído - ANTAC, 2016)
Abstract The aim of this paper is to determine the effect of adding 0.1 wt% of synthetic termite saliva on a fine and clayey sand latosol (76.5% sand) from the region of Bauru, SP (Brazil), stabilized with 1% to 3% of cement. Compacted cylindrical specimens (with standard Proctor energy) were tested to determine their compressive strength and water absorption. The results indicate that the use of the chemical stabilizer increased by at least 35% the compressive strength and reduced by up to 13% the water absorption of the samples. This work contributes to efforts aimed at reducing the consumption of cement through the production of stabilized compressed earth blocks and bricks (CEB) and rammed earth.

Resumo Este trabalho apresenta um estudo realizado para avaliar o efeito da adição de 0,1% em massa de baba de cupim sintética em um latossolo arenoargiloso fino (76,5% de areia), proveniente da região de Bauru, SP, Brasil, estabilizado com 1% a 3% de cimento. Foram ensaiados corpos de prova cilíndricos (compactados com energia Proctor normal) para determinar sua resistência à compressão e sua absorção de água. Os resultados indicam que o uso do aditivo produziu aumento de pelo menos 35% na resistência à compressão e reduziu em até 13% a absorção de água das amostras. O trabalho contribui com os esforços de redução do consumo de cimento na construção civil, através da produção de blocos (e tijolos) de terra comprimida (BTC) estabilizada e taipa.
Influência da adição de baba de cupim sintética na resistência à compressão e absorção de água de solo-cimento compactado
Keywords: Earthen architecture and construction; Compacted soil-cement; Synthetic termite saliva; Compressive strength; Water absorption; Arquitetura e construção com terra; Solo-cimento compactado; Baba de cupim sintética; Resistência à compressão; Absorção de água